Life patterns in contemporary society: a conceptual and operational proposal - Mauritti, R; Martins, SC; Costa, AF (Full Papers of the 9th Conference of the European Sociological Association, 2009)
Is it possible to draw a picture of the of life patterns in the contemporary Portuguese society? Such a picture will inevitably be a simplified summary: from the outset it must take account of the global context in which it exists and with which it has a multiplicity of relationships. As has been mentioned in a number of different of ways, this global context is that of a society increasingly driven by science-based technological innovation and the multiplication of social networks that tend to form on the most varied scales, notably on a planetary scale. In this context, the economic, political and cultural situations characterising cities, regions, countries and continents change their relative weight within the fabric of global interrelations and interdependencies. We are also witnessing the emergence of a very wide range of new goods, new accesses and new opportunities, alongside an array of gaps, risks, conflicts and institutional and identity tensions and the exponential intensification of human pressure on the environment and natural resources. Social recomposition is a fundamental element of these processes of change on a world scale. It includes very important aspects of recomposition from the geographical and age-group points of view: longer life spans, alterations in the relative weight of the various age brackets, urbanisation, and internal and international migration. It also includes the profound and comprehensive educational, occupational, socio-economic and socio-cultural recomposition that is taking place, with great intensity, in the most diverse areas of the planet and in the world as a whole. This process of recomposition also affects the levels and distribution of resources (economic, cultural and social) and relationships with institutions (inclusion and exclusion; subjection and citizenship; publics and specialists). Ways of life are modified by the combined action of alterations in the work and family spheres, markets and the welfare state. Ways of life change in accordance with the dynamics of homogenisation, diversification and recombination and of traditionalism, cosmopolitanism and syncretism. In this contemporary global context, as just described in very broad terms, how do the life patterns of the Portuguese configure? An attempt will be made below to provide some answers, not just of an impressionistic nature but on the basis of theoretical conceptualisation and empirical research. These contributions follow the line of a vast array of research on social structures and social recomposition that various CIES-ISCTE researchers have developed over a considerable period in connection with a variety of specific subjects of study on different scales